2019
DOI: 10.1111/fare.12406
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Women's Perceptions of Their Maritally Violent Fathers

Abstract: Objective To qualitatively examine fathering and father–child relationships from the perspective of young adult women who grew up with maritally violent fathers. Background Maritally violent men are consistently described as volatile, unresponsive, self‐centered, and often abusive. Yet domestic violence (DV) perpetrators are not homogenous, suggesting that maritally violent fathers may not be homogenous either. The revised tripartite model of father involvement and Johnson's typology of DV were applied to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Future research should also delve deeper into the role and meaning of fatherchild, sibling, and close peer relationships for young persons exposed to IPV. Given the literature suggesting that fathers with a history of IPV can be volatile, controlling, and lack warmth and responsiveness (Haselschwerdt et al, 2019), further investigation is warranted as these findings directly contradict the perspectives of our study participants who relayed the positive role played by fathers in their lives.…”
Section: Limitations and Future Directionsmentioning
confidence: 57%
See 2 more Smart Citations
“…Future research should also delve deeper into the role and meaning of fatherchild, sibling, and close peer relationships for young persons exposed to IPV. Given the literature suggesting that fathers with a history of IPV can be volatile, controlling, and lack warmth and responsiveness (Haselschwerdt et al, 2019), further investigation is warranted as these findings directly contradict the perspectives of our study participants who relayed the positive role played by fathers in their lives.…”
Section: Limitations and Future Directionsmentioning
confidence: 57%
“…This is a remarkable finding that highlights the importance of investigating the protective role of both siblings and fathers in promoting resilience in young persons exposed to IPV. Unfortunately, with the exception of a few small studies Haselschwerdt et al, 2019;Piotrowski, Tailor, & Cormier, 2014), these relationships are often overlooked in research with this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson's typology was developed and has been tested most often using data from women's reports on cohabiting and marital relationships, including such relationships at the time of separation (e.g., Beck et al, 2013;Johnson et al, 2014;Kelly & Johnson, 2008;Nielsen et al, 2015;Rossi et al, 2020). Although there is an emerging body of research on dating violence, relatively few studies test the applicability of Johnson's typology to dating violence (examples of exceptions include Haselschwerdt et al, 2019;Messinger et al, 2014;Zweig et al, 2014). Studies that apply Johnson's typology do not often seek to extend the typology, thus classifying only violent relationships as Johnson's typology does not include nonviolent CC absent the use of violence; moreover, such studies often focus on intimate terrorism and situational couple violence, excluding classification of mutual violent control and violent resistance altogether (e.g., Bubriski-McKenzie & Jasinski, 2014;Johnson et al, 2014;Nielsen et al, 2015).…”
Section: Extending Johnson's Typologymentioning
confidence: 99%
“…The effects on child abuse remained after controlling for physical violence severity (Emery et al, 2015). Qualitative analysis (k = 3) found that compared to those exposed to non-CC IPV, interparental CC was associated with frequent and severe child abuse, and disengaged, harsh, restrictive, and volatile paternal behaviors (Haselschwerdt et al, 2019(Haselschwerdt et al, , 2020. Intervening and being directly victimized during fatherperpetrated violence toward mothers was more common among the CC-exposed compared to non-CC IPV exposed (Haselschwerdt et al, 2019).…”
Section: Parenting and Parent-child Relationshipmentioning
confidence: 99%